Oceanic anoxic event 2 in Sergipe-Alagoas Basin, Brazil: New paleoecological insights from calcareous nannofossils assemblages - R. Jr. Silva; E. Erba; A. de Moraes Rios-Netto; C. S. Silva; T. D. Alves; A. L. Gatto Motta; B. Valle; F. Borghi Abbotts-Queiroz (Marine Micropaleontology, 2023)
A boring core (UFRJ-2-LRJ-01-SE) from the Sergipe-Alagoas Basin, Brazil, is one of the best and most expanded sections of the late Albian–early Turonian age within South America and includes one of the few records of Oceanic Anoxic Event 2 (OAE 2) in the South Atlantic Ocean. The aim of this study is to revise the calcareous nannofossil biostratigraphy and reconstruct paleoclimatic-paleoceanographic patterns based on the quantitative analysis of nannofossil assemblages performed on 78 samples throughout the core UFRJ-2-LRJ-01-SE. The biostratigraphic revision corroborates the previously defined late Albian–early Turonian age for the studied section, however, a hiatus (~ 4.7 Ma) has been identified, omitting the latest Albian–early Cenomanian time interval including OAE 1d. In addition, we confirm the occurrence of the OAE 2 interval within the studied section. Also, the revised nannofossil biostratigraphy integrated with chemostratigraphy pointed out the pres- ence of the Middle Cenomanian Event (MCE), previously identified as the Lower Cenomanian Anoxic Event (LCAE). The relative abundances of selected calcareous nannofossil taxa suggest a prevalence of warmer surface waters during the late Albian and cooler conditions during the middle Cenomanian–early Turonian. The inte- gration of diversity, species richness, Shannon diversity, equitability, nutrients (NI) and temperature (TI) indices separated four intervals recording different paleoecological conditions. The comparison with western Tethys data shows similarity between the temperature and fertility trends recognized in the studied section, suggesting global climate changes and similar fluctuations in ocean fertility during the late Albian–early Turonian.